Purification and characterization of acidic lipase from aspergillus niger NCIM 1207 - Mhetras, Nutan; Bastawade, Kulbhushan B.; Gokhale, D. V. (Bioresource Technology, 2009)
An extracellular lipase from Aspergillus niger NCIM 1207 has been purified to homogeneity using ammonium sulfate precipitation followed by phenyl sepharose and Sephacryl-100 gel chromatography. This protocol resulted in 149 fold purification with 54% final recovery. The purified enzyme showed a prominent single band on SDS-PAGE. The purified enzyme is a monomeric protein of 32.2 kDa molecular weight and exhibits optimal activity at 50 degrees C. One interesting feature of this enzyme is its highly acidic pH optimum. The isoelectric point (pl) of lipase was 8.5. The purified lipase appears to be unique since it cleaved triolein at only 3-position releasing 1,2-diolein. Chemical modification studies revealed that His, Ser, Carboxylate and Trp are involved in catalysis. (c) 2008 Elsevier Ltd. All rights reserved.
Keywords: Acidic lipase; Aspergillus niger; Positional specificity

Lipase of aspergillus niger NCIM 1207: a potential biocatalyst for synthesis of isoamyl acetate - Mhetras, Nutan; Patil, Sonal; Gokhale, Digambar V. (Indian Journal of Microbiology, 2010)
Commercial lipase preparations and mycelium bound lipase from Aspergillus niger NCIM 1207 were used for esterification of acetic acid with isoamyl alcohol to obtain isoamyl acetate. The esterification reaction was carried out at 30 degrees C in n-hexane with shaking at 120 rpm. Initial reaction rates, conversion efficiency and isoamyl acetate concentration obtained using Novozyme 435 were the highest. Mycelium bound lipase of A. niger NCIM 1207 produced maximal isoamyl acetate formation at an alcohol/acid ratio of 1.6. Acetic acid at higher concentrations than required for the critical alcohol/acid ratio lower than 1.3 and higher than 1.6 resulted in decreased yields of isoamyl acetate probably owing to lowering of micro-aqueous environmental pH around the enzyme leading to inhibition of enzyme activity. Mycelium bound A. niger lipase produced 80 g/l of isoamyl acetate within 96 h even though extremely less amount of enzyme activity was used for esterification. The presence of sodium sulphate during esterification reaction at higher substrate concentration resulted in increased conversion efficiency when we used mycelium bound enzyme preparations of A. niger NCIM 1207. This could be due to removal of excess water released during esterification reaction by sodium sulphate. High ester concentration (286.5 g/l) and conversion (73.5%) were obtained within 24 h using Novozyme 435 under these conditions.
Keywords: Aspergillus niger NCIM 1207; Fusel oil; Isoamyl acetate formation; Mycelium bound lipase; Novozyme 435

Purification and characterization of an extracellular beta-xylosidase from Pseudozyma hubeiensis NCIM 3574 (PhXyl), an unexplored yeast - Mhetras, Nutan; Liddell, Susan; Gokhale, Digambar (AMB Express, 2016)
This paper reports on the production of beta-xylosidase from an unexplored yeast, Pseudozyma hubeinsis. The expression of this enzyme could be induced by beech wood xylan when the yeast was grown at 27 degrees C. The enzyme was purified to homogeneity as a glycoprotein with 23 % glycosylation. The purification protocol involved ammonium sulphate precipitation, QAE-Sephadex A50 ion exchange chromatography and sephacryl-200 column chromatography which resulted in 8.3-fold purification with 53.12 % final recovery. The purified enzyme showed prominent single band on SDS-PAGE. It is a monomeric protein of 110 kDa molecular weight confirmed by SDS-PAGE followed by MALDI-TOF mass spectrometry (112.3 kDa). The enzyme was optimally active at 60 degrees C and pH 4.5 and stable at pH range (4-9) and at 50 degrees C for 4 h. Chemical modification studies revealed that active site of the purified enzyme comprised of carboxyl, tyrosine and tryptophan residues. The carboxyl residue is involved in catalysis and tryptophan residue is solely involved in substrate binding. The best match from the search of the NCBInr database was with gi vertical bar 808364558 glycoside hydrolase of Pseudozyma hubeiensis SY62 with 26 % sequence coverage confirming that it is a glycoside hydrolase/beta-glucosidase. From the search of customized SWISSPROT database, it was revealed that SWISSPROT does not contain any entries that are similar to the purified enzyme.

Cold active lipases: biocatalytic tools for greener technology - Mhetras, Nutan; Mapare, Vidhyashri; Gokhale, Digambar (Applied Biochemistry and Biotechnology, 2021)
Lipases are enzymes that catalyze the ester bond hydrolysis in triglycerides with the release of fatty acids, mono- and diglycerides, and glycerol. The microbial lipases account for \$400 million market size in 2017 and it is expected to reach \$590 million by 2023. Many biotechnological processes are expedited at high temperatures and hence much research is dealt with thermostable enzymes. Cold active lipases are now gaining importance in the detergent, synthesis of chiral intermediates and frail/fragile compounds, and food and pharmaceutical industries. In addition, they consume less energy since they are active at low temperatures. These cold active lipases have not been commercially exploited so far compared to mesophilic and thermophilc lipases. Cold active lipases are distributed in microbes found at low temperatures. Only a few microbes were studied for the production of these enzymes. These cold-adapted enzymes show increased flexibility of their structures in response to freezing effect of the cold habitats. This review presents an update on cold-active lipases from microbial sources along with some structural features justifying high enzyme activity at low temperature. In addition, recent achievements on their use in various industries will also be discussed.
Keywords: Cold active lipases; Frail compounds; Psychrophilic microbes; Synthesis of chiral molecules

Sustainable biodiesel production: importance of feedstock resources and production methods - Mhetras, Nutan; Gokhale, Digambar (RSC Advances, 2025)
Biodiesel made from renewable feedstock can be considered as a renewable and sustainable alternative to fossil fuels. This review briefly covers the historical background on biodiesel and discusses the various renewable feedstock sources for biodiesel production. It also emphasizes the importance of not only the feedstock quality but also on biodiesel quality that satisfies the ASTM D6751 and EN 1421 standards. In addition, the review describes various methods for biodiesel production with major thrust on transesterification, which is the key process. It also highlights the use of different types of catalysts including acidic, basic, bi-functional, and enzymes in the transesterification reaction. The review concludes by emphasizing the importance of pursuing further research and development to address the challenges in developing low cost and eco-friendly processes for biodiesel production.